Work Meaningfulness and Effort - Femke Cnossen; Milena Nikolova (Global Labor Organization (GLO), 2024)
Self-determination theory posits that individuals are motivated at work when their inherent psychological needs for competence, autonomy, and relatedness are satisfied. Drawing on this theory, this paper presents a new conceptual model explaining how work meaningfulness influences effort at work. In our model, motivation decreases the disutility of exerting effort and paves the way for experiencing meaningful work, which, in turn, boosts effort. We find empirical support for our model's propositions using new data from the Dutch LISS panel. Specifically, work meaningfulness is positively associated with effort. We also show that selfdetermination enhances work meaningfulness, especially for individuals experiencing high levels of competence, autonomy, and relatedness. Overall, our findings suggest that satisfying workers' psychological needs from working enhances work meaningfulness, motivation, and effort, providing valuable insights for economic models of effort and productivity.
Keywords: J01; J30; J32; J81; I30; I31; M50; 330; Meaningful work; Motivation; Non-monetary benefits of work; Labor market outcomes; Self-determination theory